2018
DOI: 10.1002/smtd.201800094
|View full text |Cite
|
Sign up to set email alerts
|

Various Structures of 2D Transition‐Metal Dichalcogenides and Their Applications

Abstract: 2D transition‐metal dichalcogenides (TMDs), which exhibit fascinating and fantastic properties, have promising applications in future electronic devices and photoelectric devices. Here, the recent research on 2D TMDs is summarized, including single components, 2D doped TMDs, and 2D van der Waals heterostructures. The physical picture, synthetic methods, and optoelectronic properties of these 2D materials are comprehensively described. Opportunities and emerging applications of 2D materials in the future are br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 174 publications
(313 reference statements)
3
76
0
Order By: Relevance
“…[54] In Wang's work, the phase transition and occupancy of the intercalated Na + were directly clarified by using aberration-corrected scanning transmission electron microscope (Figure 3b). [21] Besides the metal ions, nonmetal atoms such as H, O, and N were also incorporated into TMD nanosheets to achieve special properties and enhanced applications. [55] Lei et al reported a general strategy for ion-functionalization on TMD nanosheets without structural alteration by a Lewis acid-base reaction on lone pair electrons.…”
Section: Element Doping With Ions and Atomsmentioning
confidence: 99%
See 2 more Smart Citations
“…[54] In Wang's work, the phase transition and occupancy of the intercalated Na + were directly clarified by using aberration-corrected scanning transmission electron microscope (Figure 3b). [21] Besides the metal ions, nonmetal atoms such as H, O, and N were also incorporated into TMD nanosheets to achieve special properties and enhanced applications. [55] Lei et al reported a general strategy for ion-functionalization on TMD nanosheets without structural alteration by a Lewis acid-base reaction on lone pair electrons.…”
Section: Element Doping With Ions and Atomsmentioning
confidence: 99%
“…[21] As reported, thiol ligand modifications can readily occur on both internal and perimeter edges of MoS 2 nanosheets due to their higher molecular III: Hybridization of protons and semiconductor nanostructures on g-C 3 N 4 nanosheets g-C 3 N 4 Protons Sonication-driven exfoliation of g-C 3 N 4 in 10 m HCl Biosensor New heparin sensing platform with a detection limit of 18 ng mL −1 [163] g-C 3 N 4 Co 2 P nanorods Sonication-driven embedding of Co 2 P nanorods into g-C 3 N 4 nanosheets HER High H 2 production rate at 53.3 µmol g −1 h −1 (no H 2 evolution observed by using g-C 3 N 4 alone) [170] Li + battery Reversible capacity of 800 mA h g −1 at a current density of 100 mA g −1 , and no capacity drop over 500 charge/discharge cycles at a current density of 400 mA g −1 [240] affinities. [21] As reported, thiol ligand modifications can readily occur on both internal and perimeter edges of MoS 2 nanosheets due to their higher molecular III: Hybridization of protons and semiconductor nanostructures on g-C 3 N 4 nanosheets g-C 3 N 4 Protons Sonication-driven exfoliation of g-C 3 N 4 in 10 m HCl Biosensor New heparin sensing platform with a detection limit of 18 ng mL −1 [163] g-C 3 N 4 Co 2 P nanorods Sonication-driven embedding of Co 2 P nanorods into g-C 3 N 4 nanosheets HER High H 2 production rate at 53.3 µmol g −1 h −1 (no H 2 evolution observed by using g-C 3 N 4 alone) [170] Li + battery Reversible capacity of 800 mA h g −1 at a current density of 100 mA g −1 , and no capacity drop over 500 charge/discharge cycles at a current density of 400 mA g −1 [240] affinities.…”
Section: Surface Modification With Organic Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the related experiment report is rare, mainly due to the complex and inapplicable preparation method of MoS 2 / GR heterostructure. [32] Vacuum deposition techniques are not practical for creating battery electrode materials, and the conventional mixing inevitably leads to the agglomeration of the same 2D components. [21] Recently, several groups have synthesized the MoS 2 /GR heterostructure by self-assembly approaches in solution.…”
Section: Introductionmentioning
confidence: 99%
“…2D nanostructured semiconductors are distinguished transistor materials that confine the electron migration to a 2D region mainly along the long axis direction of the nanobelt. 2D nanomaterials can also closely contact metal electrodes and facilitate control of the channel structure in the FET sensor, which has attracted extensive attention . ZnO nanobelts (ZnO‐NBs) are typical 2D nanostructured semiconductors, and sensors based on ZnO transistors have been used as temperature sensors, photodetector sensors, and pH sensors with excellent performances …”
Section: Introductionmentioning
confidence: 99%